The Relationship Between Adversity Quotient (AQ) and Empty Nest Syndrome in Elderly Women in Larangan Village, Sidoarjo - Mochamad Zainul; Lely Ika Mariyati (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to examine the relationship between adversity quotient and empty nest syndrome in elderly women in Larangan village, Sidoarjo. The hypothesis in this study is that there is a negative relationship between adversity quotient and empty nest syndrome in elderly women in Larangan Sidoarjo village, namely the higher the adversity quotient of elderly women, the lower the empty nest syndrome of elderly women, and vice versa. This study uses a correlational quantitative approach with a sample of elderly women in Larangan Village, Sidoarjo, with a total sample of 199 from a total population of 424 elderly. In this study, two scales were used, the adversity quotient variable using the adversity quotient scale and the empty nest syndrome. Hypothesis analysis was performed using Pearson's product moment correlation technique on SPSS version 20.0 for windows. Based on the results of the study, the correlation coefficient (r) between adversity quotient and empty nest syndrome in elderly women in Larangan Sidoarjo village was (r) = -0.441, with a significant value (p) = 0.000 (p <0.05) and the test results coefficient of determination 0.194 (adjusted R Square) which indicates that the hypothesis of this study is accepted, namely there is a relationship between adversity quotient and empty nest syndrome in elderly women in Larangan Sidoarjo Village and Adversity Quotient provides an effective contribution of 19.4% to the Empty nest variable. syndrome and 80.6% were influenced by other factors, such as gender, age, spirituality, etc.